Laser Emission at 675 nm: Molecular Counteraction of the Aging Process - Lorenzo Notari; Laura Pieri; Francesca Cialdai; Irene Fusco; Chiara Risaliti; Francesca Madeddu; Stefano Bacci; Tiziano Zingoni; Monica Monici (Biomedicines)
Background/Objectives: Many lasers applied in skin rejuvenation protocols show emissions with wavelengths falling in the red or near-infrared (NIR) bands. To obtain further in vitro data on the potential therapeutic benefits regarding rejuvenation, we employed a 675 nm laser wavelength on cultured human dermal fibroblasts to understand the mechanisms involved in the skin rejuvenation process’s signaling pathways by analyzing cytoskeletal proteins, extracellular matrix (ECM) components, and membrane integrins. Methods: Normal human dermal fibroblasts (NHDFs) were irradiated with a 675 nm laser 24 h after seeding, and immunofluorescence microscopy and Western blotting were applied. Results: The results demonstrate that the laser treatment induces significant changes in human dermal fibroblasts, affecting cytoskeleton organization and the production and reorganization of ECM molecules. The cell response to the treatment appears to predominantly involve paxillin-mediated signaling pathways. Conclusions: These changes suggest that laser treatment can potentially improve the structure and function of skin tissue, with interesting implications for treating skin aging.